Effects of lifestyle factors on fertility: practical recommendations for modification - Mathias Abiodun Emokpae; Somieye Imaobong Brown (Bioscientifica, 2021)
The role that lifestyle factors play in fertility issues has generated some amount of interest and questions among stakeholders. This review aims to highlight the impact of lifestyle behaviors on the fertility potential of an individual and what can be done to prevent or improve reproductive outcomes. Relevant published articles on the effect of lifestyle behaviors were obtained from Medline, Pubmed and Google scholar search engines for the study. The review of the literature indicates a negative impact of modifiable lifestyle factors such as fat-rich diets, delayed childbearing/age of starting family, smoking, alcohol misuse, sexual behavior, anxiety/depression and perception/beliefs were associated with fertility. The ensuing stress precipitates social behaviors such as excessive alcohol and caffeine consumption, tobacco smoking, misuse of recreational drugs/medications, which increases the risk of sexually transmitted diseases and infection leading to infertility. Practical recommendations to modify lifestyle behaviors and the impact of misconception of Assisted Reproductive Technology in the treatment of infertility are discussed. The need to make appropriate behavioral changes to stem the tide of infertility in Nigeria is imperative. More reproductive health education is needed to create the necessary awareness of the etiologies of infertility and the importance of in vitro fertilization treatment as a means of conceiving 'natural' babies is suggested.